Kvantitativna verižna reakcija s polimerazo - nova metoda za spremljanje poteka in zdravljenja virusnih okužb - Seme, Katja (Medicinski razgledi, 1996)
The polymerase chain reaction is a relatively new in vitro method, which uses enzymatic synthesis to amplify, in an exponential manner, specific DNA or RNA sequences. The polymerase chain reaction can be used both to detect the presence of microbial sequences and to provide a quantitative evaluation of the number of copies of the genome present. This article presents a brief overview of the principles of quantitative polymerase chain reaction, summarizes some of the application problems, and describes two recently developed simple and rapid assays for quantitative detection of hepatitis C virus and HIV RNA in serum and plasma samples. Both assays were found to be valuable tools for determining the natural history of infection, dissecting viral pathogenesis and monitoring the efficacy of therapeutic interventions.
Keywords: medicina; medicine; virus; virusi; okužbe; therapy; zdravljenje